Utilization of Spent Nickel Catalyst as Raw Material for Ni-Rich Cathode Material - Shofirul Sholikhatun Nisa; Anisa Raditya Nurohmah; Cornelius Satria Yudha; Hanida Nilasary; Hartoto Nursukatmo; Endah Retno Dyartanti; Agus Purwanto (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Spent nickel catalyst will be harmful to the environment if it is not processed or used properly. In fact, this waste still has a high nickel content. The treatment of spent nickel catalysts has been widely reported, but limited to nickel extraction. Since the lithium-ion batteries demand is continued to increase, then nickel is the most sought-after metal. Consequently, nickel from spent nickel catalysts could be developed as secondary source for lithium-ion battery cathode. This study aims to utilize spent nickel catalysts into more valuable materials. Nickel that has been extracted and mixed with Mn and Co has been used as raw material for nickel-rich cathode, namely NMC. Nickel extraction and NMC synthesis were using the acid leaching method followed by co-precipitation[WI1] [SSN2] . Based on the functional test performed in this work, nickel from spent nickel catalyst can be applied to Li-ion batteries. The sintering temperature that gives good characteristics and electrochemistry was found 820oC. The galvanostatic charge-discharge test gave specific capacity results for NMC of 110.4 mAh/g. The cycle test showed that NMC synthesized from spent nickel catalyst can be carried out up to 50 cycles with a capacity retention of 87.18%.